Pengaruh Pengembangan Karir Terhadap Loyalitas Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi Pada UMKM Roti Gembong Panglima Samarinda) - Faizah, Nur; Yudhyani, Eka; Heriyanto (Universitas Muhammadiyah Pontianak, 2026)
This study examines employee retention challenges among Generation Z in the post-pandemic SME food and beverage sector. It aims to analyze the effect of career development on employee loyalty and the mediating role of job satisfaction at Roti Gembong Panglima Samarinda. Using an explanatory quantitative design, data were collected from all 30 employees and analyzed with PLS-SEM. The results indicate that career development significantly affects job satisfaction and employee loyalty, with job satisfaction acting as a dominant complementary mediator. The findings imply that SMEs should implement transparent and satisfaction-oriented career systems to strengthen emotional commitment and reduce turnover risk.